التقييم البيئي- الصحي لوحدات معالجة النفايات الطبية الصلبة الخطرة بمحافظة المنوفية: دراسة جغرافية - محمد فرج عبد العليم علام (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2021)
تمثل النفايات الطبية الخطرة أحد أبرز المشکلات البيئية والصحية التي تواجه الکثير من المجتمعات؛ إذ إنها تتضمن أنواعًا کثيرة من النفايات السائلة والصلبة والغازية التي تؤثر سلبًا على البيئة والمجتمع بصفة عامة، والعاملين بالمؤسسات الصحية بصفة خاصة؛ إذا لم تتم إدارتها وفق منظومة بيئية متکاملة. وتعد قضية التخلص من النفايات الطبية الخطرة إحدى المشکلات التي تؤرق الجهات البيئية والصحية في مصر؛ نظرًا لقلة الإمکانيات من جانب وتدني کفاءتها من جانب آخر، مع تزايد تزايد معدلات تولد هذه النفايات عامًا بعد الآخر تبعًا لزيادة مؤسسات الرعاية الصحية جراء التزايد السکاني المضطرد، ولعل ما يجعل الأمر أکثر صعوبة هو عدم وجود وعي کافٍ بخطورتها. ويعد تقييم وحدات معالجة النفايات الطبية الصلبة الخطرة وفقًا للاشتراطات البيئية والصحية جزءًا لا يتجزأ من منظومة إدارة النفايات الطبية الخطرة، إلا أن مرحلة المعالجة هذه هي المرحلة الأخطر والأکثر تعقيدًا؛ نظرًا لکونها جسرًا بين عمليات التولد والجمع والفرز، وعملية التخلص النهائي لنواتج المعالجة. ويتألف البحث من ستة مباحث رئيسة، تناول المبحث الأول بنية منظومة وحدات المعالجة وتجهيزاتها، وتناول الثاني معدلات التولد وحجم التخلص الفعلي، وقدم المبحث الثالث تحليًلا لمعدلات التشغيل، وأُفرد الرابع لدراسة منظومة إدارة النفايات الطبية الصلبة الخطرة بالمحافظة، وقدم المبحث الخامس تقييمًا جغرافيًا لمواقع وحدات المعالجة، أما المبحث السادس فقد عرض للإدارة البيئية المستدامة للنفايات الطبية الصلبة الخطرة بالمحافظة. Hazardous medical waste is one of The most prominent Environmental and Health problems facing many societies. It includes many types of liquid, solid and gas waste That negatively affect The environment and society in general, and those working in health institutions, in particular; if not Managed according to an integrated Environmental system. The disposal of Hazardous medical waste is one of the problems That haunt environmental and health authorities in Egypt; due to the limited capabilities and their low efficiency if found. Annually, the generation of these hazardous wastes rises due to the increase in health care institutions with steady population increase. Perhaps what makes it more difficult is The lack of sufficient awareness of its danger. The evaluation of hazardous solid medical waste Treatment units according to Environmental and health requirements is an integral part of The hazardous medical waste management system, but this stage of treatment is The most dangerous and complicated stage. It is a bridge between The generation, Collection and Sorting processes, and The final disposal of treatment products. The research consisted of six main Topics. Topic one dealt with The structure of The treatment units system and its equipment, Topic two dealt with generation rates and The actual disposal volume, Topic Three presented an analysis of operating rates, Topic four was singled out to study The system of managing solid medical hazardous waste in The governorate, Topic five provided a geographical assessment of The locations of The treatment units, As for The sixth topic, it presented The sustainable Environmental management of hazardous solid Medical waste in The governorate.